2020
DOI: 10.18290/rpsych20231-2
|View full text |Cite
|
Sign up to set email alerts
|

The Polish Adaptation of the Strategic Approach to Coping Scale

Abstract: The Strategic Approach to Coping Scale (SACS) is a tool designed to measure coping strategies in terms of the Multiaxial Model of Coping. The aim of this article is to present our work towards adapting the SACS to the Polish cultural context. The Polish translation of this measure and the Rotter Incomplete Sentence Blank were applied to 1,074 Poles from 11 sample groups at risk of social exclusion. Principal component analysis performed on the data showed six components rather than the original nine. Second-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Resource loss and gain latent variables were built using 4 each randomly generated parcels. Three latent variables were built to model coping strategies, in line with the second-level analysis of the SACS subscales for Polish culture (Chwaszcz et al, 2020): (1) prosocial coping composed of social support seeking, considerate action, and assertive action; (2) antisocial coping composed of dominating action, instinctive action, and cross-loaded assertive action, and (3) avoidance, originally composed of one indicator, was modeled as composed of two parcels. The latent variable quality of life was constructed from the four quality of life domains included in the WHOQOL-BREF: physical, psychological, social relationships, and environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Resource loss and gain latent variables were built using 4 each randomly generated parcels. Three latent variables were built to model coping strategies, in line with the second-level analysis of the SACS subscales for Polish culture (Chwaszcz et al, 2020): (1) prosocial coping composed of social support seeking, considerate action, and assertive action; (2) antisocial coping composed of dominating action, instinctive action, and cross-loaded assertive action, and (3) avoidance, originally composed of one indicator, was modeled as composed of two parcels. The latent variable quality of life was constructed from the four quality of life domains included in the WHOQOL-BREF: physical, psychological, social relationships, and environment.…”
Section: Resultsmentioning
confidence: 99%
“…When answering questions, respondents referred to the general difficult life situation they had found themselves in recently. Adaptation study showed that SACS-PL has six subscales that form three second-order factors (Chwaszcz et al, 2020). In the present study, second-order latent factors were modeled using the subscales' scores from the firstorder structure.…”
Section: Copingmentioning
confidence: 90%
See 1 more Smart Citation
“…When answering questions, respondents referred to the general difficult life situation they had found themselves in recently. An adaptation study showed that the SACS-PL has six subscales that form three second-order factors [ 57 ]. In the present study, second-order latent factors were modeled using the subscales’ scores from the first-order structure.…”
Section: Methodsmentioning
confidence: 99%
“…Schwarzer and Taubert (2002) referred in their concept directly to Hobfoll's theory of resource behavior (cf. Bernat, Krzyszkowska, 2017;Chwaszcz, Bartczuk, Niewiadomska, Hobfoll & Palacz-Chrisidis, 2020). In his view, people work to acquire resources they do not have, maintain those they do have, protect resources when they are threatened, and support resources so that they can be used to their best advantage.…”
Section: Proactive Coping In the Concept Of Ralf Schwarzer And Steffen Taubertmentioning
confidence: 99%